Euthanasi : avlivning av häst - Mårtensson, Annelie; Öjersjö, Sandra (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
The term euthanasia is derived from the Greek terms eu meaning good and thanatos meaning death, "good death".